MENELADANI KEPEMIMPINAN RASULULLAH SAW DALAM MENINGKATKAN MUTU PENDIDIKAN DI MIS ABDURRAHMAN KOTA BANDUNG - Nurjamil, Endang; Supriyoso, Patria (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
Abstract There is no doubt to emulate the Prophet Muhammad SAW in living various aspects of life, including in terms of leadership. This study aims to analyze and reveal the efforts of the head of the madrasah in improving the quality of education at the Abdurrahman Private Elementary Madrasah (MIS), Bandung City, by emulating the principles of the leadership of the Prophet Muhammad SAW. The leadership of the Prophet Muhammad, known for his trustworthy, honest, fair, sincere in sacrifice, full of love and affection, hayyin, layyin, qorib, sahl, and the ability to motivate and foster the people, is the main inspiration in the implementation of management in this educational institution. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the head of the madrasah has succeeded in implementing the leadership values ​​of the Prophet Muhammad in the governance of the madrasah, which has a positive impact on improving the quality of education. The application of these values ​​includes better curriculum management, improving teacher performance, creating a conducive learning environment for students, and establishing harmonious relationships with parents of students and the surrounding community. By focusing on the Islamic leadership approach, this research is expected to contribute to the development of leadership models in other Islamic educational institutions in an effort to improve the quality of education. Abstrak Tidak ada keraguan untuk meneladani Rasulullah SAW dalam menjalani berbagai hal kehidupan, termasuk dalam hal kepemimpinan. Penelitian ini bertujuan untuk menganalisis dan mengungkap upaya kepala madrasah dalam meningkatkan mutu pendidikan di Madrasah Ibtidaiyah Swasta (MIS) Abdurrahman, Kota Bandung, dengan meneladani prinsip-prinsip kepemimpinan Rasulullah SAW. Kepemimpinan Rasulullah yang dikenal dengan sifat amanah, jujur, adil, ikhlas berkorban, penuh cinta kasih sayang, hayyin, layyin, qorib, sahl, serta kemampuan memotivasi dan membina umat menjadi inspirasi utama dalam penerapan manajemen di lembaga pendidikan ini. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kepala madrasah telah berhasil menerapkan nilai-nilai kepemimpinan Rasulullah dalam tata kelola madrasah, yang berdampak positif pada peningkatan kualitas pendidikan. Penerapan nilai-nilai tersebut mencakup pengelolaan kurikulum yang lebih baik, peningkatan kinerja guru, terciptanya lingkungan belajar yang kondusif bagi siswa serta terjalinnya hubungan yang harmonis dengan orang tua siswa dan masyarakat sekitarnya. Dengan berfokus pada pendekatan kepemimpinan Islami, studi ini diharapkan dapat memberikan kontribusi bagi pengembangan model kepemimpinan di lembaga pendidikan Islam lainnya dalam upaya meningkatkan mutu pendidikan.